PA기법을 이용한 건축공사 공종별 사망사고 예측모델 개발에 관한 연구 - 의사결정나무를 중심으로 - 최정원; 김한수; Choi, Jeong Won; Kim, Han Soo (한국건설관리학회 논문집, 22(5), 2021)
Compared with other industries, construction industry shows a higher rate of death accidents and recently companies' legal responsibilities are to be increasingly enforced. The trend causes tremendous concerns for construction firms and increases the importance of forecasting and pro-actively managing death accidents in construction fields. The objective of the study is to develop a predictive analytics model for forecasting death accidents in building projects based on a decision tree technique, which enables to forecast the probabilities of death accidents by trade. The use of the model helps to decrease risks of legal punishments and to assist the safe execution of building projects by forecasting and pro-actively managing death accidents. 건설업은 타 산업에 비해 높은 사망사고율을 보이고 있으며, 최근 사망사고에 대한 기업의 법적 책임이 강화되고 있다. 이는 건설사에게 큰 부담이 되고 있으며, 건설 사망사고에 대한 선제적 예측과 관리의 필요성을 증대시키고 있다. 본 연구의 목적은 의사결정나무를 활용하여 건축공사에서 발생할 수 있는 사망사고를 사전에 예측할 수 있는 모델을 개발하는데 있다. 본 연구에서 의미하는 사망사고 예측모델이란 건축공사의 조건에 따라 공종별로 발생할 수 있는 사망사고의 가능성(확률)을 예측하는 모델을 의미한다. 예측모델의 활용을 통한 사망사고에 대한 사전 예측과 선제적 대응은 법적 처벌을 예방하고 건축공사의 성공적인 수행이라는 측면에서 중요한 의의를 지닌다.